Quantitative determination of the number of surface active sites and the turnover frequency for methanol oxidation over bulk metal vanadates - Briand, Laura Estefania (2003)
The present work investigates the number and nature of the surface active sites, selectivity and turnover frequency towards methanol selective oxidation of a series of bulk metal vanadates. The catalysts were synthesized through an organic route and characterized by laser Raman spectroscopy, X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS) and specific surface area analysis (BET). The number of surface active sites (Ns) was determined by measuring the concentration of surface methoxy species adsorbed on the catalysts exposed to an atmosphere of 2000 ppm of methanol in helium at 100 °C. The specific activity values (TOFs) were calculated by normalizing the methanol oxidation reaction rate by the number of surface active sites probed by methanol chemisorption. The comparison of the methanol oxidation products distribution from bulk metal vanadates, pure V2O5 and corresponding metal oxides (NiO, MnO, etc.) strongly suggests that the metal vanadate catalysts consist of only surface vanadium oxide sites. The comparison of the TOF values demonstrated that bulk metal vanadates possess similar activity to monolayer vanadium oxide supported catalysts and are more active than bulk metal molybdates for methanol selective oxidation. Moreover, bulk metal vanadates are as active and selective as the commercial MoO3/Fe2(MoO4)3 catalysts at high methanol conversion. © 2002 Elsevier Science B.V. All rights reserved.